Contribution of lipids to the organelle differential profile of in vitro-produced bovine embryos - Annes, Kelly; Ferreira, Christina Ramires; Valente, Roniele Santana; Marsico, Thamiris Vieira; Tannura, Juliana Hayashi; da Silveira, Juliano Coelho; Silva, Flávio Henrique; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Mesquista, Fernando Silveira; Sudano, Mateus José (Elsevier, 2023)
Each living organism is unique because of the lipid identity of its organelles. The diverse distribution of these molecules also contributes to the role of each organelle in cellular activity. The lipid profiles of whole embryos are well documented in the literature. However, this approach can often lead to the loss of relevant information at the subcellular and consequently, metabolic levels, hindering a deeper understanding of key physiological processes during preimplantation development. Therefore, we aimed to characterize four organelles in vitro-produced bovine embryos: lipid droplets (LD), endoplasmic reticulum (ER), mitochondria (MIT), and nuclear membrane (NUC), and evaluate the contribution of the lipid species to each organelle evaluated. Expanded blastocysts were subjected to cell organelle isolation. Thereafter, lipid extraction from cell organelles and lipid analysis using the Multiple Reaction Monitoring (MRM) profiling method were performed. The LD and ER displayed a greater number of lipids (Phosphatidylcholine - PC, Ceramide - Cer, and Sphingomielin - SM) with high signal-to-noise intensities. This result is due to the high rate of biosynthesis, lipid distribution, and ability to store and recycle lipid species of these organelles. The NUC had a more distinct lipid profile than the other three organelles, with high relative intensities of PC, SM, and triacylglycerols (TG), which is consistent with its high nuclear activity. MIT had an intermediate profile that was close to that of LD and ER, which aligns with its autonomous metabolism for some classes of phospholipids (PL). Our study revealed the lipid composition of each organelle studied, and the roles of these lipids could be associated with the characteristic organellar activity. Our findings highlight the lipid species and classes that are relevant for the homeostasis and function of each associated organelle and provide tentative biomarkers for the determination of in vitro embryonic development and quality.
Keywords: Embryo; Lipids; Membrane composition; Metabolomics; Organelles